Pengaruh Peran Ganda Wanita Karir Terhadap Kesejahteraan Keluarga Dengan Religiusiyas Sebagai Variabel Moderasi (Studi Kasus: Tenaga Kependidikan Uin Sjech M. Djamil Djambek Bukittinggi) - Suryani, Zulfa; Rusyaida, Rusyaida (Jurnal Ilmiah Global Education, 2025)
The aim of this research is to analyze the influence of the Dual Role of Career Women on Family Welfare with Religiosity as a Moderating Variable on the UIN Sjech M.Djamil Djambek Bukittinggi Campus.The research method uses quantitative methods. The research was conducted at the UIN Sjech M.Djamil Djambek Bukittinggi Campus. The research data used is primary data sourced from collection using a Likert scale distributed using Google Form. The population used was 31 female respondents who were education staff at the UIN Sjech M.Djamil Djambek Bukittinggi Campus. Data analysis in this research uses SEM PLS analysis using the Smart PLS 4.0 tool. The results of the research show that the Dual Role of Career Women (X) has a significant and positive effect on Family Welfare (Y) with a T-statistic value of 2.972 <1.96 and Religiosity (Z) has a negative and significant moderating effect on the dual role of career women (X) with Welfare Families with T-statistics 2.340 < 1.96. These findings indicate that religiosity can weaken the influence of career women's dual roles on family welfare. The weaker the influence of religiosity, the more effective the contribution of career women's dual roles in improving the family's economic prosperity. The implication of this research is that religiosity encourages the dual role of career women to be able to achieve a balance between professional life and personal life so that family economic prosperity can be achieved